Metabolic and hormonal assessment of adolescent and young adult women with prior premature adrenarche - Ribeiro, Flávia Alves (2019)
OBJECTIVE: Follow-up studies of girls with premature adrenarche have reported the development of polycystic ovary syndrome, insulin resistance, and dyslipidemia and a propensity to cardiovascular disease. The aim of this study was to analyze the presence of these conditions in patients previously treated at the Universidade Federal do Triaˆngulo Mineiro. METHODS: A total of 130 medical records reported premature adrenarche. One hundred and twenty-two patients were invited to participate, of whom 54 accepted; 34 patients were selected, as they had reached their final height. Anthropometric, blood glucose, insulin, and lipid and hormonal profile (LH, FSH, estradiol, 17a-OHprogesterone, androstenedione, dehydroepiandrosterone sulfate, testosterone) data were obtained, the HOMA-IR index was calculated, and pelvic ultrasonography was performed. To characterize polycystic ovary syndrome and metabolic syndrome, the Rotterdam and International Diabetes Federation criteria, respectively, were used. Data were analyzed according to measures of dispersion, frequency and correlations of interest. RESULTS: The age of the participants ranged from 15.2 to 28.2 years/months; 23.5% of the patients were overweight, 11.8% were obese, 29.4% had a large waist circumference, and 8.8% were hypertensive. None of the patients had altered glucose levels, and insulin levels and HOMA-IR were elevated in 29.4% and 38.2% of the participants, respectively; 14.7% of the patients exhibited acanthosis nigricans. The lipid profiles of the participants were variable, and one patient (2.9%) had metabolic syndrome. Polycystic ovary syndrome was found in 41.2% of patients. CONCLUSION: The percentage of patients with polycystic ovary syndrome who also had overweight, obesity and insulin resistance corroborates the literature data about the need for follow-up aiming at interventions, especially for conditions associated with cardiometabolic risk.